Analisis Pengaruh Indikator Persepsi dan Partisipasi Layanan Bantuan Akademik Terhadap Prestasi Akademik Mahasiswa Peserta Tutorial di UPBJJ-UT Bengkulu - Mikaresti, Pamela; Nurmalia, Ana; Kristanti, Dwi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aimed to analyze the effect of indicators of student perceptions and participation in academic service assistance on student academic achievement at UPBJJ-UT Bengkulu. The research used descriptive method with a quantitative approach. sampling used the Slovin method with a total sample of 362 respondents. The research instrument used was questionnaire. The data analysis technique useed multiple linear regression which was further discussed descriptively. The results of the study showed the independent variables such as X1, X2, X3, X6, X9, X13, X20, X24, partially had a significant effect on the dependent variable (GPA). Other independent variables (X4, X5, X7, X8, X10, X11, X12, X14, X15, X16, X17, X18, X21, X22, X23) partially had no significant effect on the dependent variable (Student Achievement Index).